Correlation Between Diabetic Cognitive Impairment and Diabetic Retinopathy in Patients With T2DM by 1H-MRS - Lu, Xuefang; Gong, Wei; Wen, Zhi; Hu, Lanhua; Peng, Zhoufeng; Zha, Yunfei (Frontiers in Neurology, 2019)
Objective: To explore the correlation between diabetic cognitive impairment (DCI) and diabetic retinopathy (DR) through examining the cognitive function and the metabolism of the cerebrum in Type 2 diabetes mellitus (T2DM) by 1H-MRS. Methods: Fifty-three patients with T2DM were enrolled for this study. According to the fundus examination, the patients were divided into the DR group (n = 26) and the T2DM without DR group (T2DM group, n = 27). Thirty healthy adults were selected as a control group (HC group, n = 30). Cognitive function was measured by Montreal Cognitive Assessment (MoCA). The peak areas of N-acetylaspartate (NAA), Cho-line (Cho), Creatine (Cr), and Myo-inositol (mI) as well as their ratios were detected by proton magnetic resonance spectroscopy (1H-MRS). The difference analysis between the three groups was performed by one-way ANOVA. When p < 0.05, LSD-t was applied. A partial correlation analysis (with age as a covariate) was used to analyze the correlation between metabolites in the DR group and MoCA scores. Among all T2DM patients, Chi-square test age, gender, education level, BMI, SBP, DBP, FPG, HbA1c, TC, TG, HDL-C, LDL-C, DR, and DCI correlation were measured. Differences were statistically significant while P < 0.05. Results: 1. The scores of MoCA in the DR group or in the T2DM group were significantly less than those in the HC group (F = 3.54, P < 0.05), and the scores of MoCA in the DR group were significantly less than those in the other groups (F = 3.61, P < 0.05). 2. There were significant differences for NAA in the bilateral hippocampus in DR patients, T2DM patients, and healthy controls (P < 0.05). 3. The NAA/Cr was significantly positively correlated with the score of MoCA in DR patients' left hippocampus (r = 0.781, P < 0.01). 4. Chi-square analysis found that there was a correlation between DR and DCI (x2 = 4.6, df = 1, p = 0.032, plt: 0.05). There was no correlation between other influencing factors and DCI (P > 0.05). Conclusion: DCI is closely correlated with the DR in patients with T2DM. Hippocampal brain metabolism may have some changes in two sides of NAA in patients with DR, 1H-MRS may provide effective imaging strategies and methods for the early diagnosis of brain damage and quantitative assessment cognitive function in T2DM.